Nano flame retardant N-MX-C and application thereof
By using the nanoflame retardant N-MX@C in polylactic acid, combined with aminosilane-modified MXene and COFs, the problem of flammability and flame retardant modification of polylactic acid materials affecting the mechanical properties, and the good flame retardant performance and mechanical properties of polylactic acid composite materials are achieved.
Patent Information
- Application Number
- CN202411920754.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Polylactic acid materials are flammable. While existing flame retardant modification technologies improve flame retardant performance, they often affect their mechanical properties, making it difficult to find a balance between the two.
The nanofire retardant N-MX@C is used. This nanofire retardant combines aminosilane-modified MXene with COFs through interface assembly to form a composite nanostructure, and adds it to polylactic acid, or physically mixes it with an organic flame retardant rich in phosphorus and nitrogen before adding it to improve flame retardant and mechanical properties.
The balance between flame retardant properties and mechanical properties of polylactic acid composites is achieved, which significantly improves its flame retardant properties and tensile strength, and reduces the flue gas release rate and total flue gas volume.
Smart Images

Figure CN119735951A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano flame retardant composite materials, and specifically relates to a nano flame retardant N-MX@C and application thereof in preparing a flame retardant polylactic acid composite material. Background Art
[0002] Polylactic acid (PLA) is a new type of biodegradable material made from starch raw materials from renewable plant resources (such as corn). Starch raw materials are saccharified to obtain glucose, which is then fermented with glucose and certain strains of bacteria to produce high-purity lactic acid, and then polylactic acid of a certain molecular weight is synthesized by chemical synthesis. It has good biodegradability and can be completely degraded by microorganisms in nature after use, eventually generating carbon dioxide and water without polluting the environment. This is very beneficial to protecting the environment and is a recognized environmentally friendly material. PLA has good thermal stability, bacteria resistance, non-toxicity, no irritating odor, degradability, good biocompatibility and other characteristics, and is widely used in medicine, clothing, construction, agriculture, food packaging and automotive electronics.
[0003] Polylactic acid is a polymer material formed by polycondensation of lactic acid monomers. There are a large number of ester bonds in its molecular chain. Ester bonds are easily broken at high temperatures to generate volatile combustibles. In addition, polylactic acid is mainly composed of carbon, hydrogen, oxygen and other elements, which are easy to form combustible gases during combustion, which determines the flammability of polylactic acid. The limiting oxygen index (LOI) of pure polylactic acid is low, about 20% to 20.5%, and the vertical combustion grade is NR. During the combustion process, obvious droplets will appear, which not only aggravates the spread of the fire, but may also cause secondary damage to surrounding objects. The flammability of polylactic acid limits its application in fields with high flame retardancy requirements such as electronic product packaging and the automotive industry. Therefore, the research on flame-retardant modified polylactic acid materials is crucial.
[0004] In order to solve the flame retardant problem of polylactic acid in the prior art, a variety of new flame retardants are provided. The flame retardant properties of polylactic acid are achieved by adding flame retardants to the polylactic acid matrix. For example, the disclosed patent CN202010206590.9 is an environmentally friendly flame retardant PLA plastic and its preparation method, the disclosed patent CN202010824143.X is a composite halogen-free flame retardant plant fiber reinforced polylactic acid material and its preparation method, and the disclosed patent CN202410073119.5 is a flame retardant polylactic acid composite material and its preparation method, the disclosed patent CN202211336013.7 is an intumescent flame retardant polylactic acid with extended ignition time and its preparation method, and the disclosed patent CN202110926604.9 is a low-smoke flame retardant polylactic acid composite material and its preparation method. Although the solutions provided in these five patent documents have improved the flame retardant properties of polylactic acid to a certain extent, there is still much room for improvement.
[0005] In addition, although some existing technologies can significantly improve the flame retardant properties of polylactic acid, the addition of flame retardants has an adverse effect on the mechanical properties of polylactic acid, which limits the application scope of polylactic acid composite materials to a certain extent. For example, in the disclosed patent CN202010580169.4, a polylactic acid / nanocellulose composite material and its preparation method, when the flame retardant is added in an amount of 2wt%, the tensile strength of the polylactic acid composite material is 51MPa. Those skilled in the art know that the tensile strength of conventional polylactic acid materials without the addition of flame retardants is generally 40 to 60MPa; how to maintain or even improve the original mechanical properties while improving the flame retardant properties of polylactic acid is a technical problem that the existing technology urgently needs to solve. Summary of the invention
[0006] The present invention mainly aims at the problem of polylactic acid being flammable when exposed to fire in the prior art, and the shortcomings of the prior art solutions in improving the flame retardant properties and mechanical properties of polylactic acid, and designs a nano flame retardant N-MX@C. The nano flame retardant N-MX@C is mainly prepared by combining aminosilane-modified titanium carbide (MXene) with COFs through an interface assembly method. By adding the nano flame retardant N-MX@C to polylactic acid, a flame retardant polylactic acid composite material with good flame retardant properties and mechanical properties can be obtained. In addition, the nano flame retardant N-MX@C provided by the present invention can also be physically mixed with an organic flame retardant rich in phosphorus and nitrogen, and then added to polylactic acid to obtain an enhanced flame retardant polylactic acid composite material, which also has good flame retardant properties and mechanical properties.
[0007] In a first aspect, the present invention provides a nano flame retardant N-MX@C, wherein the nano flame retardant is a composite nanostructure prepared by combining COFs and N-MX frameworks by an interface assembly method, wherein N-MX refers to aminosilane-modified MXene; the interface assembly method comprises the following steps: step S1, dispersing N-MX in dimethyl sulfoxide (DMSO), and performing low-temperature ultrasonic stirring to uniformly disperse it; step S2, adding hexachlorocyclotriphosphazene HCCP and triethylamine, and performing low-temperature ultrasonic stirring; step S3, adding HCCP, 2,6-diaminoanthraquinone, and triethylamine dissolved in DMSO, and performing ultrasonic stirring; step S4, centrifuging, washing, and drying to obtain N-MX@C is obtained; wherein, in step S1, the mass volume ratio of N-MX to DMSO is (0.1-0.3) g:10 ml, and low temperature ultrasonic stirring is performed for 0.5-1 h; in step S2, the mass volume ratio of hexachlorocyclotriphosphazene HCCP to triethylamine is 1 g:(1-2) ml, the mass ratio of hexachlorocyclotriphosphazene to N-MX is 1:(1-2), and low temperature ultrasonic stirring is performed for 0.5-1 h; in step S3, the mass ratio of hexachlorocyclotriphosphazene HCCP to 2,6-diaminoanthraquinone is (0.4-0.8): the mass volume ratio of 1,2,6-diaminoanthraquinone to triethylamine is 1 g:(0.4-0.7) ml, and low temperature ultrasonic stirring is performed for 3-5 h.
[0008] As a preferred embodiment of the nano flame retardant N-MX@C described in the present invention, the aminosilane is one or two of 3-aminopropyltriethoxysilane, 3-aminopropyltrihydroxysilane, 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0009] As a preferred embodiment of the nano flame retardant N-MX@C of the present invention, the preparation steps of the N-MX include: dispersing MXene powder in ethanol and water; passing nitrogen and stirring at low temperature ultrasonically; then adding aminosilane, continuing to stir at low temperature ultrasonically, and washing with water and washing with ethanol by centrifugation to obtain N-MX; wherein the mass volume ratio of MXene powder to the mixed solution of ethanol and water is 1g:(200-400)ml, and the volume ratio of water and ethanol is 4:1; the volume ratio of aminosilane to the mixed solution of water and ethanol is (1-3):30, wherein the MXene nanosheet is at least one of titanium carbide nanosheet, titanium nitride nanosheet, titanium carbonitride nanosheet, zirconium carbide nanosheet, molybdenum carbide nanosheet, and vanadium carbide nanosheet, and the sheet diameter of the MXene nanosheet is 2μm-10μm, and the interlayer spacing is 100nm-200nm. Further preferably, a step of preparing the MXene powder nanosheet comprises: mixing 37% hydrochloric acid and deionized water in a volume ratio of 6:1, and then weighing lithium fluoride and carbon aluminum titanium Ti in a mass ratio of (1 to 1.5):1.3 AlC 2 The mesh size of the carbon, aluminum and titanium is 200 mesh, 400 mesh or 600 mesh, and the two are slowly added to the above mixed solution respectively, and after stirring evenly, the reaction vessel is transferred to an oil bath pot, wherein the temperature of the oil bath pot is adjusted to 35-45°C, and stirring is continued for 24-48 hours, and the obtained reaction solution is centrifuged and washed with water until the pH of the upper clear liquid after centrifugation is 6±0.2. The lower layer of precipitation is retained, and the precipitation is dissolved in deionized water and stirred at low temperature ultrasonically for 1-2 hours to make the precipitation uniformly dispersed, wherein the mass ratio of deionized water to carbon, aluminum and titanium is (250-300): 1, and then the dispersion is centrifuged to take the upper layer of liquid, and freeze-dried to obtain MXene powder nanosheets.
[0010] In a second aspect, the present invention further provides an application of the nano flame retardant N-MX@C in the preparation of a flame-retardant polylactic acid composite material, wherein the application method is to mix the nano flame retardant N-MX@C and the polylactic acid after drying the polylactic acid, and then press the plate to obtain the flame-retardant polylactic acid composite material, preferably, the amount of the nano flame retardant N-MX@C added is 2wt% of the total mass. It should be noted that the total mass here refers to the total mass of the polylactic acid raw material and the nano flame retardant after removing the water.
[0011] In the third aspect, the present invention also provides a reinforced flame-retardant polylactic acid composite material prepared by simultaneously incorporating the above-mentioned nano flame retardant N-MX@C and an organic flame retardant into polylactic acid, that is, the reinforced flame-retardant polylactic acid composite material is in addition to the above-mentioned nano flame retardant N-MX@C and an organic flame retardant is also incorporated, and the nano flame retardant and the organic flame retardant FR are mixed by a physical mixing method, and preferably, the addition amount of the two flame retardants is 2wt% of the total mass.
[0012] Preferably, the preparation steps of the organic flame retardant include: mixing acetonitrile, an organic amine compound, and triethylamine in a mass ratio of (25-35):1:(2-4), maintaining the solution temperature at 5-15°C and stirring evenly; slowly adding a phosphorus-chlorine bond-rich modifier dissolved in acetonitrile to the above solution, wherein the mass ratio of the phosphorus-chlorine bond-rich modifier to the amine compound is 1:(1-3), and the mass ratio of acetonitrile to the phosphorus-chlorine bond-rich modifier is (2-3):1; heating to 60°C and stirring for 3-5 hours; heating to 80°C and stirring for 3-5 hours; separating the organic phase, washing, and drying to obtain the organic flame retardant. The organic amine compound is one or two of anhydrous piperazine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, dicyandiamide, and hexamethylenetetramine; the modifier rich in phosphorus-chlorine bonds is one of phenylphosphoryl dichloride, dichlorophosphate, phenylphosphonic acid dichloride, phosphorus oxychloride, and phosphorus pentachloride. Further preferably, when stirring at low temperature, the temperature is controlled at about 10°C. Further preferably, when slowly dropping a mixture of phenylphosphoryl dichloride and acetonitrile, the dropping time is roughly controlled to 1 to 2 hours. Further preferably, the specific operation of heating and stirring is: moving the reaction to an oil bath, first raising the temperature of the oil bath to 60°C and stirring for 3 hours, and then adjusting the temperature of the oil bath to 80°C and stirring for 3 hours. Further preferably, the washing process is specifically: washing three times with 15 ml of distilled water and 15 ml of petroleum ether. Further preferably, the specific conditions for drying are: drying in an oven at 80°C for 12 hours. Further preferably, during the plate pressing process, the temperature of the plate vulcanizer is adjusted to 180° C., and the hot pressing time is 10 to 15 minutes.
[0013] As a preferred embodiment of the present invention, the preparation steps of the flame-retardant polylactic acid composite material or the enhanced flame-retardant polylactic acid composite material include: drying the polylactic acid in an oven at 60-100°C for 12 to 24 hours to remove moisture in the polylactic acid; placing the polylactic acid in an internal mixer of a torque rheometer and kneading it for 4 to 6 minutes; then placing the nano flame retardant described in the second aspect or the two flame retardants described in the third aspect in the internal mixer of the torque rheometer and kneading it for 10 to 15 minutes to evenly mix the polylactic acid and the flame retardant; placing the evenly mixed polylactic acid and flame retardant materials into an iron mold and hot pressing them in a flat vulcanizer; removing the hot-pressed composite material, cooling and solidifying it, and obtaining a polylactic acid flame-retardant composite material.
[0014] Optimally, the temperature of the torque rheometer and the plate vulcanizer was adjusted to 180 °C.
[0015] Optimized, during the internal mixing process, the temperature of the torque rheometer zones 1, 2, and 3 should be adjusted to 180°C, the time of polylactic acid in the internal mixer should be 4 to 6 minutes to completely melt the polylactic acid, and the internal mixing should be 10 to 15 minutes after adding the flame retardant to evenly mix the flame retardant and polylactic acid.
[0016] Principle of the invention:
[0017] MXene is a two-dimensional transition metal carbonitride with high thermal stability and a tightly packed layer structure. This structure enables MXene to effectively block the transfer of heat and the spread of flames during combustion, thus playing a flame retardant role. MXene decomposition product TiO 2 It has excellent catalytic activity and can promote the carbonization of polymer matrix. This catalytic carbonization can form a protective layer to further prevent the spread of flames and the transfer of heat, thereby improving the flame retardant properties of the material. In addition, MXene nanosheets and their decomposition products TiO 2 A "maze" structure can be constructed in the polymer matrix to extend the gas diffusion path. This physical barrier effect can effectively prevent the diffusion of oxygen and combustible gases, thereby reducing the combustion rate and improving the flame retardant effect. However, the thermal oxygen stability of MXene is relatively poor, especially under the condition of coexistence of water and oxygen, oxidation reaction is prone to occur. This oxidation reaction will cause the structure of the MXene nanosheets to change, thereby affecting its flame retardant properties. Therefore, when using MXene as a flame retardant, special attention should be paid to protecting it from oxidation to improve the flame retardant effect and service life. In addition, due to the high surface energy of MXene nanosheets, it is easy to agglomerate and stack, resulting in uneven dispersion in the polymer matrix. This uneven dispersion state will affect the flame retardant properties of MXene and reduce the overall flame retardant effect of the material. In this way, the present invention uses aminosilane to modify MXene, improve its compatibility and interfacial interaction force with the polymer matrix, and can be more effectively dispersed in the polymer matrix to avoid the occurrence of agglomeration. This helps to improve the mechanical properties and processing properties of the composite material, and is also conducive to the improvement of flame retardant properties. Aminosilane-modified MXene can be added to the polymer matrix as a flame retardant to improve the flame retardancy of the composite material through its physical barrier effect and chemical inhibition effect. The two-dimensional layer structure of MXene can form an effective physical barrier to prevent the spread of flames and heat. At the same time, the amino functional groups in aminosilane and the metal catalytic sites of MXene can promote the carbonization of the polymer matrix, forming a more complete and denser carbon layer, further improving the flame retardancy.
[0018] COFs are crystalline organic frameworks with a network structure composed of covalent bonds. They have the characteristics of porosity, crystallinity and structural diversity. They have high thermal stability and can maintain structural stability at high temperatures, thereby slowing down the combustion process. By designing the COFs structure, flame retardant elements such as phosphorus and nitrogen can be introduced to improve the flame retardant properties of the material. Combining COFs with N-MX, the synergistic effect between them can further enhance the flame retardant properties of the material. The two-dimensional sheet structure of MXene can form a physical barrier to block the transfer of heat and the release of smoke. At the same time, the porous structure of COFs can also slow down the diffusion of gases during combustion. N-MX contains abundant metal catalytic sites that can catalyze the formation of carbon layers. During the combustion process, the flame retardant functional groups in COFs release non-combustible gases, thereby diluting the combustible gases and interrupting the free radical chain reaction in the combustion, reducing the combustion rate. In addition, in order to further improve the flame retardant properties of polylactic acid, as a more preferred embodiment, in addition to adding the above-mentioned nano flame retardant to polylactic acid, an organic flame retardant rich in phosphorus and nitrogen can also be mixed at the same time, and it can be physically mixed with the nano flame retardant to further enhance the flame retardant effect.
[0019] The beneficial effects of the present invention are embodied in:
[0020] 1. Prior art 1, namely, the published patent CN202010206590.9, an environmentally friendly flame-retardant PLA plastic and its preparation method, when the flame retardant is added at 5wt%, the peak heat release rate and the total heat release are reduced by 27% and 21% respectively, and when the flame retardant is added at 4wt%, the peak heat release rate and the total heat release are reduced by 45.4% and 43.9% respectively. This shows that the prepared flame retardant has good flame retardant properties.
[0021] 2. Prior art 2, namely the published patent CN202010580169.4, a polylactic acid / nanocellulose composite material and its preparation method, when the flame retardant is added in an amount of 2wt%, the tensile strength of the polylactic acid composite material is 51MPa. When the flame retardant of the present invention is added in an amount of 2wt%, the tensile strength of the composite material is 66.5MPa. This shows that the prepared polylactic acid flame-retardant composite material has good mechanical properties.
[0022] 3. Prior art 3, namely the published patent CN202010824143.X, a composite halogen-free flame-retardant plant fiber reinforced polylactic acid material and its preparation method, when the flame retardant is added in an amount of 2wt%, its oxygen index is 25.7%. When the flame retardant of the present invention is added in an amount of 2wt%, its oxygen index is 26.4%, indicating the good flame retardancy of the prepared material.
[0023] 4. Prior art 4, namely the disclosed patent CN202410073119.5, a flame-retardant polylactic acid composite material and its preparation method, when the flame retardant addition amount is 5wt%, the oxygen index of the composite material is 26.3%. When the flame retardant addition amount of the present invention is 4wt%, the oxygen index of the composite material is 28.8%, indicating that the prepared composite material has good flame retardant properties.
[0024] 5. Prior art 5, namely the published patent CN202211336013.7, a kind of intumescent flame-retardant polylactic acid with prolonged ignition time and preparation method, when the addition amount of flame retardant is 5wt%, the peak heat release rate of flame-retardant polylactic acid material is 354.4kW / m 2 The total heat released is 67.8MJ / m 2 When the addition amount of the flame retardant of the present invention is 4wt%, the peak heat release rate of the flame retardant polylactic acid material is 321.75kW / m 2 The total release is 49.77MJ / m 2 .
[0025] 6. Prior art 6, namely the disclosed patent CN202110926604.9, a low-smoke flame-retardant polylactic acid composite material and its preparation method, when 1wt% titanium carbide nanosheets and 14wt% silicone gel microencapsulated ammonium polyphosphate are added, the peak smoke release rate and total smoke release of the flame-retardant polylactic acid material are reduced by 20.2% and 21.6% respectively compared with the pure polylactic acid material. After adding 2wt% N-MX@CB and 2wt% organic flame retardant FR in the present invention, the peak smoke release rate and total smoke release decreased by 58.2% and 45.5%. The results show that the flame-retardant polylactic acid material in the present invention has lower smoke toxicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1a The electron microscope image of COFs prepared in comparative example 1;
[0027] Figure 1b The electron microscope image of N-MX prepared in comparative example 2 is shown;
[0028] Figure 1c This is an electron microscope image of N-MX@CA prepared in Example 1;
[0029] Figure 1d Elemental mapping spectrum and EDS results of N-MX@CA prepared in Example 1;
[0030] Figure 2a TEM image of MXene prepared in a specific embodiment;
[0031] Figure 2b TEM image of N-MX prepared in comparative example 2;
[0032] Figure 2c TEM image of COFs prepared in comparative example 1;
[0033] Figure 2d TEM image of N-MX@CA prepared in Example 1;
[0034] Figure 2e This is an enlarged TEM image of N-MX@CA prepared in Example 1;
[0035] Figure 2f TEM image of N-MX@CB prepared in Example 2;
[0036] Figure 2g Elemental mapping spectrum and EDS results of N-MX@CA prepared in Example 1;
[0037] Figure 3a The TGA curves of commercially available pure PLA and the flame-retardant PLA composite materials prepared in Application Examples 1-3 and Comparative Application Examples 1-2 under nitrogen atmosphere;
[0038] Figure 3b for Figure 3a The enlarged view of the TGA curve in the temperature range of 310℃~365℃;
[0039] Figure 3c for Figure 3a The enlarged view of the TGA curve in the temperature range of 700℃ to 800℃;
[0040] Figure 3d DTG curves of commercially available pure PLA and flame-retardant PLA composite materials prepared in Application Examples 1-3 and Comparative Application Examples 1-2;
[0041] Figure 4a The heat release rate curves of cone calorimetry tests of commercially available pure PLA and the flame-retardant PLA composite materials prepared in Application Examples 1-3 and Comparative Application Examples 1-2;
[0042] Figure 4b It is the total heat release curve of cone calorimetry test of commercially available pure PLA and flame-retardant PLA composite materials prepared in Application Examples 1-3 and Comparative Application Examples 1-2;
[0043] Figure 4c The smoke release rate curves of cone calorimetry tests of commercially available pure PLA and the flame-retardant PLA composite materials prepared in Application Examples 1-3 and Comparative Application Examples 1-2;
[0044] Figure 4d It is the total smoke production curve of the cone calorimetry test of the commercially available pure PLA and the flame-retardant PLA composite materials prepared in Application Examples 1-3 and Comparative Application Examples 1-2;
[0045] Figure 4e The CO generation rate curves of the cone calorimetry test of commercially available pure PLA and the flame-retardant PLA composite materials prepared in Application Examples 1-3 and Comparative Application Examples 1-2;
[0046] Figure 4f Cone calorimetry test of total CO release curves of commercially available pure PLA and flame-retardant PLA composite materials prepared in Application Examples 1-3 and Comparative Examples 1-2;
[0047] Figure 4g Cone calorimetry test of CO2 of commercially available pure PLA and flame-retardant PLA composites prepared in Application Examples 1-3 and Comparative Examples 1-2 2 Generate rate curves;
[0048] Figure 4h Cone calorimetry test of CO2 of commercially available pure PLA and flame-retardant PLA composites prepared in Application Examples 1-3 and Comparative Examples 1-2 2 Total release curve;
[0049] Figure 5 is the oxygen index of the commercially available pure PLA and the PLA composite materials prepared in Application Examples 1-3 and Comparative Application Examples 1-2;
[0050] Figure 6 It is the tensile strength of the PLA composite material prepared by commercially available pure PLA and Application Examples 1-3 and Comparative Application Examples 1-2. DETAILED DESCRIPTION
[0051] In order to further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. Based on the examples in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0052] Meanwhile, the raw materials or reagents mentioned below that are not described in detail are all commercially available products, and the process steps or methods that are not described in detail are all process steps or methods known to those skilled in the art.
[0053] The sources of some raw materials and reagents involved in the following embodiments and test examples are as follows:
[0054] Ethanol was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0055] 3-Aminopropyltriethoxysilane was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0056] Dimethyl sulfoxide was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0057] Hexachlorocyclotriphosphazene was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0058] Triethylamine was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0059] 2,6-Diaminoanthraquinone was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0060] Methanol was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0061] Acetonitrile was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0062] Anhydrous piperazine was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0063] Phenylphosphoryl dichloride was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0064] Petroleum ether was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0065] Polylactic acid (PLA) 4032D was purchased from Shanghai Jujia Plastic Raw Materials Co., Ltd.
[0066] The MXene used in the following Example 1 is prepared by etching. The specific preparation process is: first, use a measuring cylinder to measure 90 ml of 37% hydrochloric acid, and then continue to add deionized water to the measuring cylinder until 105 ml. Put them together in a plastic bottle, stir them on a magnetic stirrer, and seal the bottle mouth with a sealing film. Then weigh 5g of lithium fluoride and slowly add it to the plastic bottle. After stirring evenly, weigh 4g of 400 mesh Ti 3 AlC 2 , and slowly add it to the plastic bottle and stir evenly. After stirring evenly, move it to an oil bath pot, set the oil bath pot temperature to 40℃ and stir for 48h, then centrifuge and wash the stirred mixture with water, where the centrifuge speed is set to 3500rpm, the time is 5min, and wash with water until the pH of the supernatant after centrifugation is 6, and then centrifuge the precipitate according to Ti 3 AlC 2 The MXene dispersion was prepared by dispersing the MXene in deionized water at a mass ratio of 1:250 and ultrasonically stirring the MXene in an ice bath for 1 hour. The dispersion after ultrasonication was then centrifuged and the upper liquid after centrifugation was collected to obtain a MXene dispersion. The dispersion was placed in a freeze dryer for drying to obtain a MXene powder.
[0067] Example 1 Preparation of N-MX@CA
[0068] Step S1, preparation of N-MX: 1 g of MXene powder was dispersed in a mixture of 300 ml of ethanol and water, wherein the volume ratio of ethanol to water was 1:4. The mixture was kept under ultrasonic stirring at low temperature for 1 hour, and then 10 ml of 3-aminopropyltriethoxysilane was added, and then kept under low temperature stirring for 24 hours, and then centrifuged and washed with water and ethanol, and then placed in a vacuum oven at 60°C for 6 hours to obtain N-MX.
[0069] Step S2, preparation of N-MX@CA: 0.2 g N-MX was dispersed in 20 ml DMSO, and ultrasonic stirring was maintained for 30 minutes. Then, 0.2 g HCCP and 0.2 ml triethylamine were added, and ultrasonic stirring was continued for 30 minutes. Then, 0.35 g HCCP, 0.56 g 2,6-diaminoanthraquinone, and 0.3 ml triethylamine were added to 40 ml DMSO. Then, the mixed DMSO was added to the above solution, and ultrasonic stirring was performed at room temperature for 3 hours. The reacted solution was centrifuged, washed, and dried to obtain N-MX@CA.
[0070] Example 2 Preparation of N-MX@CB
[0071] Step S1, preparation of N-MX: 1 g of MXene powder was dispersed in a mixture of 300 ml of ethanol and water, wherein the volume ratio of ethanol to water was 1:3. The mixture was kept under ultrasonic stirring at low temperature for 1 hour, and then 15 ml of γ-aminopropyltriethoxysilane was added, and then kept under low temperature stirring for 24 hours, and then centrifuged and washed with water and ethanol, and then placed in a vacuum oven at 60°C for 5 hours to obtain N-MX.
[0072] Step S2, preparation of N-MX@CB: 0.4 g N-MX was dispersed in 20 ml DMSO, and ultrasonic stirring was maintained for 30 minutes. Then, 0.2 g HCCP and 0.2 ml triethylamine were added, and ultrasonic stirring was continued for 30 minutes. Then, 0.35 g HCCP, 0.56 g 2,6-diaminoanthraquinone, and 0.3 ml triethylamine were added to 40 ml DMSO. Then, the mixed DMSO was added to the above solution, and ultrasonic stirring was performed at room temperature for 3 hours. The reacted solution was centrifuged, washed, and dried to obtain N-MX@CB.
[0073] Example 3 Preparation of organic flame retardant (FR)
[0074] First, 156g of acetonitrile, 5.16g of anhydrous piperazine, and 13.4g of triethylamine were mixed in a flask, and the mixed solution was stirred at 10°C for 1h. Then 12.9g of phenylphosphoryl dichloride was dissolved in 31.2g of acetonitrile, and the mixed solution was slowly added dropwise to the above solution, and the dropping time was roughly controlled at 2h. After the dropwise addition was completed, the flask was moved to an oil bath, and the temperature was raised to 60°C for 3h, and then the temperature of the oil bath was raised to 80°C for another 3h. After the reaction was completed, the organic phase was separated, washed three times with 15ml of distilled water and 15ml of petroleum ether respectively, and then evaporated and dried in an oven at 80 degrees. An organic flame retardant FR was obtained.
[0075] Preparation of COFs by Comparative Example 1
[0076] First, 2.1 g HCCP, 3.36 g 2,6-diaminoanthraquinone, and 1.8 ml triethylamine were added to 100 ml DMSO, and then ultrasonically stirred (160 W, 40 kHz) at room temperature for 3 hours. The product was washed with methanol and ethanol, and dried at 60 degrees for 3 hours to obtain COFs.
[0077] Preparation of N-MX by Comparative Example 2
[0078] 1g MXene powder was dispersed in 300ml of a mixture of ethanol and water, where the volume ratio of ethanol to water was 1:4. The mixture was kept under ultrasonic stirring at low temperature for 1h, and then 10ml of 3-aminopropyltriethoxysilane was added, and then kept under low temperature stirring for 24h, and then centrifuged and washed with water and ethanol, and then placed in a vacuum oven at 60℃ and dried for 6h to obtain N-MX.
[0079] Figure 1a The SEM image of COFs is shown, and it can be seen that there is an obvious three-dimensional framework structure in the image. Figure 1b The SEM image of N-MX is shown. It can be seen that the material is flaky and the surface is relatively smooth, without any agglomerated framework structure. Figure 1c This is the SEM image of N-MX@CA. It can be seen that the surface of the flakes is relatively rough and distributed with some three-dimensional framework structures, indicating that the COFs structure and N-MX are well combined. Figure 1d These are the element diffraction spectrum and EDS results of N-MX@CA. EDS shows that the main elements distributed in N-MX@CA are C, O, N, Ti, P, Si and other elements. The element diffraction spectrum shows that the elements Ti, C, O, P, N and other elements are evenly distributed, indicating the uniform combination of COF structure on N-MX structure.
[0080] Figure 2a This is a TEM image of MXene, showing a very smooth surface. Figure 2bThis is the TEM image of N-MX, which shows a partially wrinkled lamellar structure, indicating the successful modification of MXene by 3-aminopropyltriethoxysilane. Figure 2c This is the TEM image of COFs, which shows a relatively rough structure. Figure 2d This is the TEM image of N-MX@CA. It can be seen that some rough structures are evenly distributed on the flakes, indicating that the COFs structure is successfully combined with N-MX. Figure 2e This is the TEM magnified image of N-MX@CA, in which N-MX can be seen as indicated by the dotted line. Figure 2f is the TEM image of N-MX@CB, which is similar to Figure 2d resemblance. Figure 2g are the elemental diffraction spectrum and EDS results of N-MX@CA, which show the uniform distribution of elements such as Ti, C, O, P, N, and Si.
[0081] Application Example 1 Preparation of PLA / 2.0N-MX@CA
[0082] Before the experiment, polylactic acid (PLA) was first dried in an oven at 60°C for 24 hours to remove the moisture inside. The temperature of the torque rheometer zones 1, 2, and 3 and the flat vulcanizer was adjusted to 180°C. Weigh 49g of polylactic acid, add the polylactic acid to the internal mixer of the torque rheometer, and mix it at a speed of 60rpm for 5min to completely melt the PLA. Weigh 1g of N-MX@CA powder, add it to the internal mixer and mix it for 10min to mix the powder and PLA evenly. Then take out the mixed composite, put it into the mold, place the mold on the flat vulcanizer for hot pressing, and finally take out the mold and cool it to solidify the composite material. PLA / 2.0N-MX@CA is obtained.
[0083] Application Example 2 Preparation of PLA / 2.0N-MX@CB
[0084] Before the experiment, polylactic acid (PLA) was first dried in an oven at 60°C for 24 hours to remove the moisture inside. The temperature of the torque rheometer zones 1, 2, and 3 and the flat vulcanizer was adjusted to 180°C. Weigh 49g of polylactic acid, add the polylactic acid to the internal mixer of the torque rheometer, and mix it at a speed of 60rpm for 5min to completely melt the PLA. Weigh 1g of N-MX@CB powder, add it to the internal mixer and mix it for 10min to mix the powder and PLA evenly. Then take out the mixed composite, put it into the mold, place the mold on the flat vulcanizer for hot pressing, and finally take out the mold and cool it to solidify the composite material. PLA / 2.0N-MX@CB is obtained.
[0085] Application Example 3 Preparation of PLA / 2.0N-MX@CB / 2.0FR
[0086] Before the experiment, polylactic acid (PLA) was first dried in an oven at 60°C for 24 hours to remove the moisture inside. The temperature of the torque rheometer zones 1, 2, and 3 and the flat vulcanizer was adjusted to 180°C. Weigh 48g of polylactic acid, add the polylactic acid to the internal mixer of the torque rheometer, and mix it at a speed of 60rpm for 5min to completely melt the PLA. Weigh 1g of N-MX@CB powder and 1g of organic flame retardant FR, add them together to the internal mixer and mix for 15min to mix the powder and PLA evenly. Then take out the mixed compound, put it into the mold, place the mold on the flat vulcanizer for hot pressing, and finally take out the mold and cool it to solidify the composite material. PLA / 2.0N-MX@CB / 2.0FR is obtained.
[0087] Preparation of PLA / 2.0N-MX using Comparative Example 1
[0088] Before the experiment, polylactic acid (PLA) was first dried in an oven at 60°C for 24 hours to remove the moisture inside. The temperature of the torque rheometer zones 1, 2, and 3 and the flat vulcanizer was adjusted to 180°C. Weigh 49g of polylactic acid, add the polylactic acid to the internal mixer of the torque rheometer, and mix it at a speed of 60rpm for 5min to completely melt the PLA. Weigh 1g of N-MX powder, add it to the internal mixer and mix it for 10min to mix the powder and PLA evenly. Then take out the mixed compound, put it into the mold, place the mold on the flat vulcanizer for hot pressing, and finally take out the mold and cool it to solidify the composite material. PLA / 2.0N-MX is obtained.
[0089] Preparation of PLA / 2.0 COFs using Comparative Example 2
[0090] Before the experiment, polylactic acid (PLA) was first dried in an oven at 60°C for 24 hours to remove the moisture inside. The temperature of the torque rheometer zones 1, 2, and 3 and the flat vulcanizer was adjusted to 180°C. Weigh 49g of polylactic acid, add the polylactic acid to the internal mixer of the torque rheometer, and mix it at a speed of 60rpm for 5min to completely melt the PLA. Weigh 1g of COFs powder, add it to the internal mixer and mix it for 10min to mix the powder and PLA evenly. Then take out the mixed composite, put it into the mold, place the mold on the flat vulcanizer for hot pressing, and finally take out the mold and cool it to solidify the composite material. PLA / 2.0 COFs is obtained.
[0091] Figure 3a , Figure 3b , Figure 3cThe TGA test results of pure PLA and flame-retardant PLA composites under nitrogen. The test results show that the residual carbon rate of pure PLA is 0.2wt%, and the residual carbon rates of PLA / 2.0 COFs, PLA / 2.0 N-MX, PLA / 2.0 N-MX@CA, and PLA / 2.0 N-MX@CB are 0.94wt%, 1.24wt%, 2.06wt%, and 1.56wt%, respectively. Figure 3d This is the DTG curve of pure PLA and flame-retardant PLA composites. The addition of flame retardant can effectively reduce the mass loss rate in the second stage.
[0092] Through cone calorimetry test, the effect of the prepared flame retardant on the combustion performance of PLA was further studied, and the commercially available PLA was compared with application examples 1 to 3 and application comparative examples 1 to 2. The cone calorimetry test results are mainly as follows: Figure 4a Shown is the heat release rate; Figure 4b Shown is the total heat release; Figure 4c Shown is the smoke production rate; Figure 4d The total smoke production is shown; Figure 4e Shown is the CO generation rate; Figure 4f The total CO release is shown; Figure 4g The CO 2 Spawn rate; Figure 4h The CO 2 From these results, it can be seen that the peak heat release rate, total heat release, peak smoke generation rate and total smoke production of pure PLA are 589.03kW / m 2 、88.64MJ / m 2 、0.0088m 2 / s, 0.11m 2 The peak CO generation rate and the total CO release were 0.0039 g / s and 0.82 g, respectively. 2 Peak generation rate and CO 2 The peak heat release rate, total heat release, peak smoke generation rate and total smoke production, peak CO generation rate, total CO release, and CO 2 Peak generation rate and CO 2 The total release is 402.06kW / m 2 、61.28MJ / m 2 、0.00542m 2 / s, 0.09m 2, 0.00171g / s, 0.56g, 0.369g / s and 56.66g, which were reduced by 31.7%, 30.9%, 38.4%, 18.2%, 56.2%, 31.7%, 23.0% and 20.2%, respectively. The peak heat release rate, total heat release, peak smoke generation rate and total smoke production, peak CO generation rate, total CO release, and CO 2 Peak generation rate and CO 2 The total release is 364.55kW / m 2 、52.38MJ / m 2 、0.00415m 2 / s、0.1m 2 , 0.00176 g / s, 0.47 g, 0.354 g / s and 52.51 g, which were reduced by 38.1%, 40.9%, 54.5%, 9.1%, 54.9%, 42.7%, 26.1% and 26.1%, respectively. The peak heat release rate, total heat release, peak smoke generation rate and total smoke production, peak CO generation rate, total CO release, and CO 2 Peak generation rate and CO 2 The total release is 321.75kW / m 2 、49.77MJ / m 2 、0.00368m 2 / s, 0.06m 2 , 0.00186g / s, 0.42g, 0.296g / s and 46.28g, respectively, reduced by 45.4%, 43.9%, 58.2%, 45.5%, 52.3%, 48.8%, 38.2%, 34.8%. These results show that the use of the flame retardant provided by the present invention can effectively inhibit the release of heat and smoke during the combustion of PLA. In addition, although the flame-retardant polylactic acid composite material prepared by comparative examples 1 to 2 is compared with the commercially available PLA in terms of heat release rate, total heat release, smoke production rate, total smoke production, CO generation rate, CO 2 Peak generation rate and CO 2 The total release amount has significant performance advantages, but compared with the flame-retardant polylactic acid composite materials provided in Application Examples 1 to 2, there are still some shortcomings, especially in the heat release rate and the total heat release amount. The flame-retardant polylactic acid composite materials prepared by using Comparative Examples 1 to 2 are also much higher in smoke production rate and total smoke production in the initial stage of combustion than those of Application Examples 1 to 2 of this application; as for the enhanced flame-retardant polylactic acid composite material provided in Application Example 3 of this application, no matter which aspect of the flame retardant performance is compared with Application Comparative Examples 1 to 2, it has significant technical advantages.
[0093] The limiting oxygen index (LOI) refers to the minimum oxygen concentration required for a material to burn with a flame in an oxygen-nitrogen mixed gas flow under specified conditions. It is expressed as the volume percentage of oxygen. A high oxygen index means that the material is not easy to burn, and a low oxygen index means that the material is easy to burn. Figure 5 The oxygen index results of pure PLA, flame retardant PLA composite materials provided by comparative examples 1 to 2 and application examples 1 to 3 are given. It can be seen that with the addition of flame retardant, the oxygen index of the composite material has been significantly improved, especially the flame retardant PLA composite materials provided by application examples 1 to 3 have significant advantages over pure PLA and comparative examples 1 to 2, indicating that the composite material prepared in this application has more excellent flame retardancy.
[0094] Figure 6 The tensile strength results of pure PLA, flame retardant PLA composite materials provided by comparative examples 1 to 2 and application examples 1 to 3 are given. It can be seen that the addition of flame retardant effectively improves the tensile strength of polylactic acid, especially the flame retardant PLA composite materials provided by application examples 1 to 3 have significant advantages over pure PLA and comparative examples 1 to 2, indicating that the composite materials prepared in this application have more excellent mechanical properties.
[0095] Therefore, considering the flame retardant properties and mechanical properties, the flame retardant polylactic acid composite material and the reinforced flame retardant polylactic acid composite material provided in the present application have significant performance advantages over pure PLA and the flame retardant polylactic acid composite material with single-component flame retardant additions prepared in comparative examples 1 to 2.
Claims
1. A nano flame retardant N-MX@C, characterized in that: The nano flame retardant is a composite nanostructure prepared by combining COFs and N-MX framework by interfacial assembly, wherein the N-MX refers to aminosilane-modified MXene.
2. A nano flame retardant as claimed in claim 1, characterized in that: The interface assembly method comprises the following steps: step S1, dispersing N-MX in dimethyl sulfoxide (DMSO), and stirring at low temperature and ultrasonically to make it dispersed evenly; step S2, adding hexachlorocyclotriphosphazene HCCP and triethylamine, and stirring at low temperature and ultrasonically; step S3, adding HCCP, 2,6-diaminoanthraquinone, and triethylamine dissolved in DMSO, and stirring ultrasonically; step S4, centrifuging, washing, and drying to obtain N-MX@C; wherein, in step S1, the mass volume ratio of N-MX to DMSO is (0.1 to 0.3) g: 10ml, low temperature ultrasonic stirring for 0.5-1h; in step S2, the mass volume ratio of hexachlorocyclotriphosphazene HCCP to triethylamine is 1g: (1-2)ml, the mass ratio of hexachlorocyclotriphosphazene to N-MX is 1: (1-2), and low temperature ultrasonic stirring is 0.5-1h; in step S3, the mass ratio of hexachlorocyclotriphosphazene HCCP to 2,6-diaminoanthraquinone is (0.4-0.8): the mass volume ratio of 1,2,6-diaminoanthraquinone to triethylamine is 1g: (0.4-0.7)ml, and low temperature ultrasonic stirring is 3-5h.
3. A nano flame retardant as claimed in claim 1, characterized in that: The aminosilane is one or two of 3-aminopropyltriethoxysilane, 3-aminopropyltrihydroxysilane, 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
4. A nano flame retardant as claimed in claim 1, characterized in that: The preparation steps of the N-MX include: dispersing MXene powder in ethanol and water; passing nitrogen and stirring at low temperature with ultrasonic method; then adding aminosilane, continuing to stir at low temperature with ultrasonic method, washing with water and washing with ethanol by centrifugation to obtain N-MX; wherein the mass volume ratio of MXene powder to the mixed solution of ethanol and water is 1g:(200-400)ml, and the volume ratio of water and ethanol is 4:1; the volume ratio of aminosilane to the mixed solution of water and ethanol is (1-3):30, wherein the MXene nanosheet is at least one of titanium carbide nanosheet, titanium nitride nanosheet, titanium carbonitride nanosheet, zirconium carbide nanosheet, molybdenum carbide nanosheet and vanadium carbide nanosheet, and the sheet diameter of the MXene nanosheet is 2μm-10μm, and the interlayer spacing is 100nm-200nm.
5. A nano flame retardant as claimed in claim 1, characterized in that: The steps of preparing the MXene powder nanosheets include: mixing 37% hydrochloric acid and deionized water in a volume ratio of 6:1, then weighing lithium fluoride and carbon aluminum titanium Ti3AlC2 in a mass ratio of (1-1.5):1, wherein the mesh size of the carbon aluminum titanium is 200 mesh, 400 mesh or 600 mesh, and slowly adding the two to the mixed solution respectively, and stirring the mixture evenly, transferring the reaction container to an oil bath, wherein the temperature of the oil bath is adjusted to 35-45°C, and stirring is continued for 24-48 hours, and the obtained reaction solution is centrifuged and washed with water until the pH of the upper clear liquid after centrifugation is 6±0.2; retaining the lower precipitate, dissolving the precipitate in deionized water and stirring at low temperature ultrasonically for 1-2 hours to make the precipitate evenly dispersed, wherein the mass ratio of deionized water to carbon aluminum titanium is (250-300):1, and then centrifuging the dispersion to obtain the upper liquid, and freeze-drying to obtain the MXene powder nanosheets.
6. Use of the nano flame retardant N-MX@C according to claim 1 in the preparation of flame-retardant polylactic acid composite materials.
7. The use according to claim 6, characterized in that The application method is that after the polylactic acid is dried, the nano flame retardant N-MX@C described in claim 1 and the polylactic acid are mixed by banburying, and then pressed into plates to obtain a flame-retardant polylactic acid composite material.
8. The use according to claim 6, characterized in that The added amount of the nano flame retardant N-MX@C is 2 wt % of the total mass.
9. A reinforced flame-retardant polylactic acid composite material, characterized in that: In addition to the nano flame retardant N-MX@C described in claim 1, the reinforced flame retardant polylactic acid composite material also incorporates an organic flame retardant FR. The nano flame retardant and the organic flame retardant FR are mixed by a physical mixing method. The preparation steps of the organic flame retardant include: acetonitrile, an organic amine compound, and triethylamine are mixed in a mass ratio of (25-35):1:(2-4), and the solution temperature is maintained at 5-15°C and stirred evenly; a modifier rich in phosphorus-chlorine bonds dissolved in acetonitrile is slowly added dropwise to the above solution, and the modifier rich in phosphorus-chlorine bonds and the amine compound are mixed. The mass ratio of acetonitrile to the modifier rich in phosphorus-chlorine bonds is 1: (1-3), and the mass ratio of acetonitrile to the modifier rich in phosphorus-chlorine bonds is (2-3): 1; the temperature is raised to 60°C and stirred for 3-5 hours; the temperature is raised to 80°C and stirred for 3-5 hours; the organic phase is separated, washed and dried to obtain an organic flame retardant; the organic amine compound is one or two of anhydrous piperazine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, dicyandiamide, and hexamethylenetetramine; the modifier rich in phosphorus-chlorine bonds is one of phenylphosphoryl dichloride, dichlorophosphate, phenylphosphonic acid dichloride, phosphorus oxychloride, and phosphorus pentachloride.
10. The reinforced flame-retardant polylactic acid composite material according to claim 9, characterized in that: The addition amount of the two flame retardants, namely the nano flame retardant and the organic flame retardant FR, is 2 wt % of the total mass.
Citation Information
Patent Citations
Environment-friendly flame-retardant PLA plastic and preparation method thereof
CN111454547A
Polylactic acid / nanocellulose composite material and preparation method thereof
CN111690240A
A compound halogen-free flame-retardant plant fiber reinforced polylactic acid material and its preparation method
CN111793338B
A low-smoke flame-retardant polylactic acid composite material and its preparation method
CN113549310B
Intumescent flame-retardant polylactic acid with prolonged ignition time and preparation method of intumescent flame-retardant polylactic acid
CN117903581A
Cited By
Waterborne acrylate antistatic coating as well as preparation method and application thereof
CN120310352A